Advertisement call of Rhinella major (Anura: Bufonidae) from the lower Amazonas River basin with comments on intraspecific variation - Bernardes, Cyro De Sousa; Carvalho, Thiago Ribeiro De; Giaretta, Ariovaldo Antonio (Zootaxa, 2015)
The Rhinella granulosa group currently comprises 13 species that are distributed throughout South America, and Panama (Sanabria et al. 2010; Pereyra et al. 2015). Rhinella major (Müller & Hellmich) is a widely distributed species that occurs in the Chaco of Argentina e Paraguay, Brazilian and Bolivian Cerrado, as well as open environments along the Madeira, Tapajós, and Xingú rivers, reaching the mouth of the Amazon River (Narvaes & Rodrigues 2009).